BIOGAS PRODUCTION FROM A MIXTURE OF COW MANURE WITH CHICKEN MANURE - Denta Sanjaya (The University of Lampung, 2015)
Biogas technology with zero waste concept is expected to be the alternative energy and to reduce environmental problems. The purpose of this study is to know the biogas yield per kilogram of each chicken and cow manure comparison. The study was conducted in six treatments with the addition of chicken manure of 0, 100, 300, 500, 700 and 1000 grams. The fermentation process is done using a batch system and biogas measurement was taken daily. The parameters to be observed were organic matter, the degree of acidity (pH), temperature, volume of biogas, biogas productivity, and C / N ratio of each treatment. The results showed that the overall pH at the beginning and end of the study tend to be close to neutral. The highest biogas yield was resulted from a mixture of chicken manure and cow manure at the composition of 1:1 or 50%:50% with biogas total amount of 35.690 ml and biogas productivity of 0,33 liters/g (volatile solid) . Keywords : biogas, cow manure, chicken manure, anaerobic codigestion.